Conventional and automated diagnostic methods - Johnson, Alan (Henry Stewart Talks, 2010)
Antibiotic susceptibility testing: rationale, Disc susceptibility test, Determination of MICs, Broth vs. agar dilution, Standardizing methods, BSAC standardized testing method, BSAC vs. CLSI, MIC determination by E-test, MICs of multiple antibiotics for the same bacterial strain, Testing E. coli, Interpretation of susceptibility tests, Defining susceptibility and resistance, European Committee on Antimicrobial Susceptibility testing (EUCAST), EUCAST MIC breakpoints, Clinical breakpoints, Microbiological breakpoints, Establishing breakpoints, Automating antibiotic susceptibility testing, Vitek 2 AST system, Advanced expert system, Interpretive reading: the limits, The future